Development of a psychological support system for skiers based on biopsychosocial factors - Zebzeev, V.; Sokolovskaia, S.; Fedoseev, A.; Finogenov, A. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to develop a model of psychological support for the training of ski jumpers based on biopsychosocial factors.